Spatial analysis of urban integration and dispersion on traffic flows to Villavicencio along the old road and the new road to Bogotá (Colombia) (2022)
An analysis is made of the existing relationship between two urban sectors of Villavicencio and the road to the Llano, particularly those that allow access (exit and entrance) via the old road (OR) and the new road (NR) to the city. This, from technical procedures and some elements referenced in the spatial syntax (SS), through the use of topological measurements and the analysis of what happens in each place. Describing the urban morphological processes reflected in the number of roads, intersections and the built areas that conform these urban spaces and provide a kind of language that allows identifying some kind of pattern to explain, from a part of the physical elements of the city, the degree of connection or isolation between urban territories with the periphery: a socio-spatial sign.  The use of color ranges as indicators of the intensity of integration in the maps, as well as geometric elements of the distribution of nodes and intersections, number of lines and nodes associated with the distance of the roads, among others, support the analysis of each sector, define focal points in each one and correspondence between the hierarchy of roads and the levels of urban functionality. The expansion and fragmentation around the implementation of the road are assumed as particular spatial phenomena that are behind the social integration or dispersion of the sector.